Response to 'Position statement on ethics, equipoise and research on charged particle therapy'. - Jones, B; Howick, J; Hopewell, J; Liew, S (2014)
In August 2011, a group of medical doctors, ethicists, academic and medical physicists were asked to debate and reach consensus on the potential need for randomised control trials to test charged particle radiation therapy (CPRT) for treating tumours. The outcome of the meeting was a paper recently published in the Journal of Medical Ethics entitled "Position statement on ethics, equipoise and research on charged particle therapy" by Sheehan et al. However 6 of the 30 meeting participants withdrew from authorship of the 'position statement' because their views were not adequately represented. The 'position statement' did not state our reasons for withdrawing from the statement, which is a considerable omission. We had two principal objections: (1) the case for the benefits to patients and society of randomized trials to test CPRT was not adequately represented, and (2) the complexities and potential harms of CPRT were not clearly stated. In this response we explain and justify our objections. Patients, doctors and policymakers seeking to make independent judgments about whether equipoise exists for the relative benefits of CPRT should therefore read this document alongside the 'position' statement.